Srednja vas v Bohinju – Palaeoenvironmental Record of Human Influence on the Lowlands of the Julian Alps - Caf, Nina (Arheološki vestnik, 2025)
In recent decades, archaeological and palynological research in the Bohinj basin has mainly focused on the highlands, while research in the valley is much older and often insufficient. In order to obtain new information about the local human impact on the environment, a palynological analysis was carried out in a marsh-like environment near Srednja vas v Bohinju. The main aim of the investigation was to obtain more information about the former vegetation, economy and use of the environment. The palynological results show an early human impact on the environment (since the Eneolithic, ca. 4700 cal. BP). In the Iron Age/Roman period, the local spruce forest was replaced by pastures, which is consistent with the archaeological sites nearby. Throughout the Middle Ages, a decline in tree taxa can be observed, which could be due to continuous pastoralism and an increasing demand for iron. In the Modern Period, the landscape remained open with continuous grazing/arable farming and indirectly due to metallurgy.